Overlooked sex and gender aspects of emerging infectious disease outbreaks: Lessons learned from COVID-19 to move towards health equity in pandemic response - Lawry, Lynn Lieberman; Lugo-Robles, Roberta; McIver, Vicki (Frontiers in Global Women's Health, 2023)
Sex and gender issues are especially important in emerging infectious diseases (EIDs) but are routinely overlooked despite data and practice. Each of these have an effect either directly, via the effects on vulnerability to infectious diseases, exposures to infectious pathogens, and responses to illness, and indirectly through effects on disease prevention and control programs. The severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), the viral agent of coronavirus disease 2019 (COVID-19) has underscored the importance of understanding the sex and gender impacts on pandemics. This review takes a broader looks at how sex and gender impact vulnerability, exposure risk, and treatment and response that affect incidence, duration, severity, morbidity, mortality, and disability of EIDs. And although EID epidemic and pandemic plans need to be “pro-women”, they need to be broader and include all sex and gender factors. Incorporation of these factors are a priority at the local, national, and global policy levels to fulfil the gaps in scientific research, public health intervention programs and pharmaceutical service strengthening to reduce emerging disease inequities in the population during pandemics and epidemics. A failure to do so creates acceptance of the inequities and infringes on fairness and human rights norms.